[PS 01-20] ROLE OF HCaRG/COMMD5 IN EPITHELIAL-MESENCHYMAL TRANSITION DURING HYPOXIA. (September 2016) - Tremblay, Johanne; Verissimo, Thomas; Campion, Carole G.; Cossette, Suzanne; Hamet, Pavel
Abstract : Objective: Hypertension plays a pivotal role in the progression of renal failure as both a cause and a consequence of renal injury. Vascular damage, inflammation and the activation of the epithelial-mesenchymal transition (EMT) lead to kidney disease. Our studies have shown that HCaRG (Hypertension-related, Calcium-Regulated Gene) is involved in renal tissue repair after ischemia-reperfusion injury in transgenic mice over-expressing HCaRG in proximal tubules (Matsuda et al. JASN, 2011). HCaRG encodes a small protein of 22.5 kDa that belongs to the COMMD family. HCaRG/COMMD5 is mainly expressed in proximal tubular cells where it promotes kidney tissue repair after injury by a mechanism resulting in a decrease in epithelial cell proliferation, increased migration, followed by cell re-differentiation (Matsuda et al. J. Nephrol. 2013). Our objective is to determine the cellular mechanisms of kidney tissue repair by HCaRG/COMMD5 after ischemia. Design and Method: To reproduce an ischemia model in vitro, human kidney cells (HK-2) were placed under hypoxic conditions (< 1% 0) or exposed to 200 μM or 400 μM of cobalt chloride for 24 hours. HCaRG silencing or overexpression experiments were conducted to determine the effect of this protein on markers of the EMT process, such as E-cadherin (epithelial) and α -SMA (mesenchymal). Results: Hypoxia and treatment of cells with cobalt chloride caused the expected EMT of HK-2 cells that was accompanied by a significant decrease of HCaRG/COMMD5 expression. Silencing of HCaRG/COMMD5 expression by its specific siRNA reduced the epithelial marker E-cadherin expression, while its overexpression by p3X-Flag hCOMMD5 plasmid induced E-cadherin expression. Together these data support a role for HCaRG in the maintenance and rescue of the epithelial phenotype after hypoxia. Conclusions: HCaRG appears to be involved in cell re-differentiation into an epithelial phenotype, an essential step required to complete the repair process after injury.